Insect succession and decomposition patterns of carcasses in Sarawak, Malaysian Borneo - Madinah, Adrus; Nor Aliza, Abdul Rahim (UMT Publisher, 2018)
Insect succession and decomposition process on three types of carcasses were conducted in peat swamp forest in Kota Samarahan, Sarawak, Malaysia, from August 2007 until January 2008. Nine fresh animal carcasses were used as carcass model in forensic entomological research. Three experiments were conducted and using three species of animals, namely plantain squirrels, Callosciurus notatus, chickens, Gallus gallus, and toads, Duttaphrynus melanostictus. The objectives of this study are to determine the decomposition stages and the insect succession with decomposition of different types of carcass in a peat swamp forest. Five decomposition stages were observed during this study which were fresh, bloated, active decay, advanced decay and dry remains stages. A total of 38 species of insects (seven Orders and 14 families) were collected from the nine carcasses. The common species that visit all three types of carcasses were Chrysomya megacephala and C. rufifacies (Calliphoridae). Ambient temperatures and relative humidity showed a reciprocal relationship in all the locations where the readings were recorded from the carcasses. These data may be used as a reference for further studies in ecology and forensic entomology in Malaysia.